(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
This article aims to explain the migration factors of the foreign population in Thailand. The migration concepts and the approach of studying the foreign population in the present Thai society found that the migration factors consisted of the need for economic security, life, good quality of life for oneself and one’s own family, marriage with a foreign spouse, leisure travel, safety in life and property, seeking business opportunities, access to property and property owners, changing lifestyle, and extending savings for investment funds. As for the guidelines for studying the foreign population, there are three frameworks to consider, which include: (1) the origin, (2) the way to the destination, and (3) the destination. The origin is the study of migration decisions, factors, and objectives. The way to the destination considers the travel process, facilitating travel according to the legal system of the origin country, and labor export policies. Finally, the destination is the study of personal and official networks, relational and contact mechanisms of the community, and lifestyle of the people in the community, including the local impact of the destination country.